2018
DOI: 10.15406/mojap.2018.05.00172
|View full text |Cite
|
Sign up to set email alerts
|

The estimation of lumbar intervertebral disc volumes before and after exercise using the Cavalieri method

Abstract: Purpose: Our aim in this study is to determine the volume differences of the lumbar intervertebral discs by using the Cavalieri method. Subjects and methods: In our study, lumbar magnetic resonance imaging (MRI) was performed on 20 male (mean age, 22 years; age range, 19-25 years) athletes without any known disease on the lumbar vertebra and discs immediately after resting and after a 50-minute loading exercise. The lumbar intervertebral disc volumes were measured by Cavalieri method and compared after resting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…The four pairs of paranasal sinuses (maxillary, sphenoidal, frontal, and ethmoidal) are not only a fundamental part of the upper airway but also contribute to the development of the jaw and face and constitute the largest air cavity of the skull. The radiographic study of the paranasal sinuses is quite frequent because they are usually the site of chronic infectious processes, allergies, hypoplasia, pneumosinus dilatans, or atelectasis [39,45]. For example, sinusitis is one of the most common paranasal diseases, affecting almost 30 million people in the United States and 11% of the European population, making it one of the main causes of antibiotics prescription [41].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The four pairs of paranasal sinuses (maxillary, sphenoidal, frontal, and ethmoidal) are not only a fundamental part of the upper airway but also contribute to the development of the jaw and face and constitute the largest air cavity of the skull. The radiographic study of the paranasal sinuses is quite frequent because they are usually the site of chronic infectious processes, allergies, hypoplasia, pneumosinus dilatans, or atelectasis [39,45]. For example, sinusitis is one of the most common paranasal diseases, affecting almost 30 million people in the United States and 11% of the European population, making it one of the main causes of antibiotics prescription [41].…”
Section: Discussionmentioning
confidence: 99%
“…A decrease in frontal sinus volume was observed in the studies of Kumar et al, 2022 [20]; Karakas and Kavakli, 2005 [27]; Tatlisumak et al, 2008 [15]; Emirzeoglu et al, 2007 [39]; and Ozdikici, 2018 [45]. In the studies of Jasso-Ramirez et al, 2022 [11]; Demiralp et al, 2019 [33]; Fatu et al, 2006 [42]; and Soman et al, 2016 [44], an increase in sinus area was observed, while Kim et al, 2010 [6]; Sahlstrand-Johnson et al, 2011 [31]; Cohen et al, 2018 [32]; Marino et al, 2020 [36]; Takahashi et al, 2016 [40]; Yilmaz et al, 2020 [12]; and Rubira-Bullen et al, 2010 [41], did not observe sinus volumetric alterations with age.…”
Section: Frontal Sinusmentioning
confidence: 97%
See 3 more Smart Citations